Help! It's parents day at dsa - Mcmullan, Kate; Basso, Bill (New York : Grosset & Dunlap, 2004)
Wiglaf faces the double embarrassment of having his wacky parents visit Dragon Slayers' Academy on Parents Day and starring in the school play as the brave but small knight, Sir Tinybottom.
Keywords: Children's stories; Action and adventure fiction